Residential Place Attachment as an Adaptive Strategy for Coping With the Reduction of Spatial Abilities in Old Age - Fornara, Ferdinando; Lai, Amanda Elizabeth; Bonaiuto, Marino; Pazzaglia, Francesca (Frontiers in Psychology, 2019)
This study intended to test whether attachment to one’s own residential place at neighborhood level could represent a coping response for the elderly (consistently with the “docility hypothesis”; Lawton, 1982), when dealing with the demands of unfamiliar environments, in order to balance their reduction of spatial abilities. Specifically, a sequential path was tested, in which neighborhood attachment was expected to play a buffer role between lowered spatial competence and neighborhood satisfaction. The participants (N=270), senior citizens (over-65 years old), responded to a questionnaire including the measures of spatial self-efficacy, spatial anxiety, attitude towards wayfinding, residential attachment and residential satisfaction. Results from the mediation analysis showed that a lower perceived spatial self-efficacy is associated to a higher spatial anxiety, and both promote a more negative attitude toward wayfinding tasks in non-familiar places. This leads to a higher attachment to one’s own neighborhood, which in turn predicts a higher residential satisfaction. Thus, the “closure” response of becoming more attached to their residential place may be an adaptive strategy of the elderly for compensating the Person-Environment (P-E) mis-fit (Lawton & Nahemow, 1973) when they feel unable (or less able) to cope with the demands of unfamiliar environments.